Studi Akidah : Konsep Teologi dalam Pemikiran Asy’ariyah, Salafi dan Wahabi - Pramita, Sindi; Ilfah, Ade; Sapri, Sapri (Darul Yasin Al Sys, 2024)
The schools of thought from Asy'ariyah, Salafiyyah, Wahabiyyah have different but still continuous backgrounds. Therefore, this discussion is to provide an explanation of where the differences lie. The aim of this research is to use the Library Research method by utilizing data and literature in this writing. Ash'ariyah ideology emerged because of differences in Hasan Al-Ash'ari's understanding of the Mu'tazilah school which became a mandatory understanding of society at that time because it was supported by the Caliphate, he used a middle method, namely sticking to the Al-Qur'an and Sunnah but not ignoring it. Sense. The Salafi ideology developed by Ibn Hambal prioritizes the Qur'an and prioritizes the companions of the prophet or Salafus Salih and puts reason aside. Meanwhile, Wahhabiyah claims that faith, knowledge, deeds and worship according to their version are true, beyond their understanding they are called infidels.